THE THREAT OF THE CURRENT MARITIME PIRACY - JUAN C. FERNÁNDEZ SANZ (Política y Estrategia, 2017)
This study aims to conduct an analysis of the current piracy situation -as defined in the UN Convention on the Law of the Sea 1982- and the International Maritime Organization’s armed robbery against ships concept. This analysis is focusing on those places in which it is more common the occurrence of these violations, such as Somalia and Southeast Asia. This study includes a statement of its causal factors, as well as a review of statistical and ‘modus operandi’ of those crimes. It will be also shown the identification of the geographical zones where the attacks at sea are more frequently. Finally it an study of the the answers and the naval operations that the international community has developed against those felonies, will be presented.